Respiratory syncytial virus infection‐induced mucus secretion by down‐regulation of miR‐34b/c‐5p expression in airway epithelial cells. Issue 21 (16th September 2020) - Du, Xizi; Yang, Yu; Xiao, Gelei; Yang, Ming; Yuan, Lin; Qin, Ling; He, Ruoxi; Wang, Leyuan; Wu, Mengping; Wu, ShuangYan; Feng, Juntao; Xiang, Yang; et al.
Abstract: Severe RSV infection is the main cause of hospitalization to children under the age of five. The regulation of miRNAs on the severity of RSV infection is unclear. The aim of the study was to identify the critical differential expression miRNAs (DE miRNAs) that can regulate the pathological response in RSV‐infected airway epithelial cells. In this study, miRNA and mRNA chips of RSV‐infected airway epithelia from Gene Expression Omnibus (GEO) were screened and analysed, separately. DE miRNAs‐targeted genes were performed for further pathway and process enrichment analysis. DE miRNA‐targeted gene functional network was constructed on the basis of miRNA‐mRNA interaction. The screened critical miRNA was also investigated by bioinformatics analysis. Then, RSV‐infected human bronchial epithelial cells (HBECs) were constructed to verify the expression of the DE miRNAs. Finally, specific synthetic DE miRNAs mimics were used to confirm the effect of DE miRNAs on the RSV‐infected HBECs. 45 DE miRNAs were identified from GEO62306 dataset. Our results showed that hsa‐mir‐34b‐5p and hsa‐mir‐34c‐5p decreased significantly in HBECs after RSV infection. Consistent with the biometric analysis, hsa‐mir‐34b/c‐5p is involved in the regulation of mucin expression gene MUC5AC. In RSV‐infected HBECs, the inducement of MUC5AC production by decreased hsa‐mir‐34b/c‐5p was partly mediated through activation of c‐Jun. These findings provide new insights into the mechanism of mucus obstruction after RSV infection and represent valuable targets for RSV infection and airway obstruction treatment.